Etika Kato Nan Ampek dalam Budaya Minangkabau: Studi Lokusi, Ilokusi dan Perlokusi - Yanti, Silvia Rahma; Amelia, Ulfi; Agustia, Dwi Putri; Susanto, Djoko (Jurusan Pendidikan Bahasa & Sastra Indonesia, Universitas Negeri Gorontalo, 2024)
The Kato nan ampek is a polite language procedure that regulates Minangkabau society in socializing. Minangkabau customs originate from Islamic teachings, which are described in the terms